SK Channels Modulation Accelerates Equilibrium Recovery in Unilateral Vestibular Neurectomized Rats - Brahim Tighilet; Audrey Bourdet; David Péricat; Elise Timon-David; Guillaume Rastoldo; Christian Chabbert (MDPI AG, 2021)
We have previously reported in a feline model of acute peripheral vestibulopathy (APV) that the sudden, unilateral, and irreversible loss of vestibular inputs induces selective overexpression of small conductance calcium-activated potassium (SK) channels in the brain stem vestibular nuclei. Pharmacological blockade of these ion channels by the selective antagonist apamin significantly alleviated the evoked vestibular syndrome and accelerated vestibular compensation. In this follow-up study, we aimed at testing, using a behavioral approach, whether the antivertigo (AV) effect resulting from the antagonization of SK channels was species-dependent or whether it could be reproduced in a rodent APV model, whether other SK channel antagonists reproduced similar functional effects on the vestibular syndrome expression, and whether administration of SK agonist could also alter the vestibular syndrome. We also compared the AV effects of apamin and acetyl-DL-leucine, a reference AV compound used in human clinic. We demonstrate that the AV effect of apamin is also found in a rodent model of APV. Other SK antagonists also produce a trend of AV effect when administrated during the acute phase of the vertigo syndrome. Conversely, the vertigo syndrome is worsened upon administration of SK channel agonist. It is noteworthy that the AV effect of apamin is superior to that of acetyl-DL-leucine. Taken together, these data reinforce SK channels as a pharmacological target for modulating the manifestation of the vertigo syndrome during APV.